Estresse e recuperação em mulheres atletas de futebol e futsal: análise da resposta inflamatória e indicadores comportamentais, neuroendócrino e bioquímico - Santos, Thaislaine dos (2019)
OBJECTIVE: The objective of the present study was to examine the influence of the preparatory period for a competition in the perception of stress and recovery by analyzing the relationship of stress and recovery with the inflammatory response and behavioral, neuroendocrine and biochemical indicators in amateur futsal athletes and female football. METHODS: Athletes were monitored for seven days. On the first day, fasting blood samples were collected for the determination of interest, in order to perform leukogram and cell culture; applied the questionnaires to evaluate the behavioral indicators: mood scale (BRUMS) to measure mood, Mini Sleep Questionnaire (MSQ) to evaluate sleep duration and quality, and the Health Condition Questionnaire to measure the symptoms of the upper respiratory tract infection (URTI) (the latter was specifically answered for seven days) and the Yo-Yo Intermittent Recovery Level 1 test (Yo-YoIR1) was performed, followed by a one-day interval. On the third day was applied RESTQ Sport-76 questionnaire to evaluate stress and recovery, performed anthropometry, body composition and squat jump performance test (SJ). The relationships between the stress and recovery dimensions and the variables of interest were tested using the Spearman correlation, with rho values considered as 0.00 - 0.30 (insignificant correlation), 0.30 - 0.50 (low correlation), 0.50-0.70 (moderate correlation), 0.70-0.90 (high correlation) and 0.9-1 (very high correlation). Statistical significance was estabilished at 5% and using the SPSS (version 22). RESULTS: Significant correlations were found for the inflammatory response: there was a negative and moderate correlation between serum interleukin-10 (IL-10) and general recovery (rho = -0.569; p-value = 0.017); low negative correlation between IL10 (STest) and sports recovery (rho = -0.493; p-value = 0.045); negative and moderate correlations between ITRS symptoms and total stress (rho= -0,614; p-valor= 0,045) and with general stress (rho = -0.612, p-value = 0.046). And for cortisol (neuroendocrine indicator), with moderate negative correlations with total stress (rho = -0.582, p-value = 0.014) and with general stress (rho = -0.622, p-value = 0.008). CONCLUSION: The preparatory period for a competition has influence on the perception of stress and recovery through the relationship with the inflammatory response and the neuroendocrine indicator in amateur athletes of futsal and female football.